Degradation of Serrate via ubiquitin-independent 20S proteasome to survey RNA metabolism - Li, Yanjun (Nat Plants, 2020)
Serrate (SE) is a key factor in RNA metabolism. Here, we report that SE binds 20S core proteasome α subunit G1 (PAG1) among other components and is accumulated in their mutants. Purified PAG1-containing 20S proteasome degrades recombinant SE via an ATP- and ubiquitin-independent manner in vitro. Notwithstanding, PAG1 is a positive regulator for SE in vivo as pag1 shows comparable molecular and /or developmental defects relative to se. Furthermore, SE is poorly assembled into macromolecular complexes exemplified by microprocessor in pag1 compared to Col-0. Intriguingly, SE overexpression triggered destruction of both transgenic and endogenous protein, leading to similar phenotypes of se and SE overexpression lines. Thus, we propose that PAG1 degrades intrinsically disordered portion of SE to secure functionality of folded SE that is assembled and protected in macromolecular complexes. This study provides new insight into how 20S proteasome regulates RNA metabolism through controlling its key factor in eukaryotes.